Treated wastewater reuse for recharge in agricultural fields: Retention dynamics and geochemical modeling of macronutrients in soils - Ajit Kumar; Basant Yadav (Agricultural Water Management)
Reusing treated wastewater (TWW) with high concentrations of macronutrients (nitrogen, phosphorus, and potassium) in Agricultural-Based Managed Aquifer Recharge (AgMAR) presents various challenges to soils, crops, water resources, microbes, public health, and economics. This study investigates the behavior of macronutrients in agricultural soil during TWW recharge through AgMAR, focusing on the effects of mineral formation during the recharge process. Batch experiments, kinetic studies, and pH edge experiments were conducted to understand the retention behaviors of ammonium (NH4+), phosphate (PO4−3), and Potassium ion (K+) in soils. Visual MINTEQ was employed to evaluate the saturation indices of nutrient dissolution, equilibrium, and precipitation conditions, using macronutrient concentrations from TWW and soil mineral data as inputs. The Freundlich isotherm model provided the best fit for the experimental results for ammonium and potassium, with correlation coefficients of 0.98 and 0.99, respectively. For phosphorus, the Temkin model showed the best fit, with a correlation coefficient of 0.96. Retention behaviors varied with pH: ammonium and potassium exhibited higher retention under basic conditions, while phosphate demonstrated greater retention in acidic conditions. The pseudo-second-order kinetic model best described the retention kinetics observed in the experiments. The saturation index (SI) results revealed that manganese hydrogen phosphate (MnHPO4) fully precipitates and calcium phosphate Ca3(PO4)2 precipitates at pH levels above 8, while other nutrients remained in dissolution. This study highlights that nutrient retention from TWW effluent enhances nutrient availability for plants. However, the precipitation of certain forms, such as MnHPO₄ and Ca₃(PO₄)₂, may clog soil pores, restricting recharge pathways. These findings support the reuse of TWW as a sustainable method for supplementing agricultural nutrients and ensuring safe groundwater recharge, while also offering a safe disposal solution for wastewater treatment plants